Clinical manifestations of nonmotor symptoms in 1021 Japanese Parkinson's disease patients from 35 medical centers. (May 2017) - Maeda, Tetsuya; Shimo, Yasushi; Chiu, Shih-Wei; Yamaguchi, Takuhiro; Kashihara, Kenichi; Tsuboi, Yoshio; Nomoto, Masahiro; Hattori, Nobutaka; Watanabe, Hirohisa; Saiki, Hidemoto; ,
Abstract: Introduction: We aimed to investigate the prevalence and severity of nonmotor symptoms (NMSs) and to identify factors affecting NMSs and the health-related quality of life of Japanese patients with Parkinson's disease (PD). Methods: A total of 1021 patients with PD who had one or more NMS and showed wearing-off under anti-parkinsonian treatment were enrolled from 35 medical centers in Japan for this observational study. The primary measurements were the Movement Disorder Society unified Parkinson's disease rating scale (MDS-UPDRS) part I and the Parkinson's Disease Questionnaire (PDQ-8). The relationships of MDS-UPDRS and PDQ-8 with the patient's clinical background and undertaken medical interventions were determined. Here, we report baseline data of our 52-week ongoing study. Results: The mean MDS-UPDRS part I and PDQ-8 scores were 10.9 and 7.3, respectively. The most common NMSs were constipation problems (85.4%), sleep problems (73.7%), pain and other sensations (72.7%) and daytime sleepiness (72.0%). Fatigue was an NMS that affected 79.6% of females but only 72.6% of males, whereas features of dopamine dysregulation syndrome affected only 5.6% of females and 10.8% of males. Positive correlations were found between the MDS-UPDRS part I and the PDQ-8 (p < 0.0001, r = 0.56) and between the number of NMSs and the PDQ-8 score (p < 0.0001, r = 0.47). Conclusions: This study revealed distinctive patterns of NMSs in Japanese patients with PD and suggested that the prevalence and severity of NMSs vary between sexes, and that the NMSs are important factors affecting the long-term quality of life of PD patients. Highlights: J-FIRST is the first large-scale observational study in Japan to assess NMSs of PD. Over 1000 patients across 35 centers were assessed using MDS-UPDRS Part I and PDQ-8. MDS-UPDRS Part I and PDQ-8 scores were positively correlated. Number of NMSs was associated with PDQ-8 score, and thus QOL. Prevalence/severity of NMSs vary by sex, clinical background, and medication.